Formação de Ilhas de Calor Urbano em áreas industriais - Arruda, Angela Maria de (Universidade Federal de São Carlos, 2023)
The impact of urbanization and industrialization on the natural environment has aroused the interest of many researchers since the end of the 19th century, when the increase in urban air temperature compared to the rural environment. This phenomenon called Urban Heat Island (UHI) impacts the thermal comfort of individuals, health problems, in air pollution and greater energy demand. The main objective of this thesis was recording the thermal behavior, occurrence and configuration of UHIs caused by the implementation of industrial zones in the urban microclimate. From the analysis systematically, it can be identified that soil use and temperature (LST) are largely explored in work on and remote sensing appears as a method most widespread, followed by computer modeling and simulation. When comparing two industrial districts of different cities, Sintra/PT and Uberlândia/BR, using the software ENVI-met and principal component analysis, it was found that the impact of ventilation in the cooling of industrial districts overlaps with factors such as the percentage of vegetation of the studied site and the albedo, capable of increasing 1.5oC in the industrial environment of Sintra when there is a reduction in wind speed of 1.9 m/s. It was verified need to expand the study, beyond the interrelationship between Tar and LST, considering other microclimatic variables such as wind speed (WS) and direction (WD), sky seeing factor (SVF), rate of kinetic energy (TKE), relative humidity (RH) and air specific (Uesp). Tar and RH were collected in situ in a residential section (R) and another industrial (DI), in the city of Uberlândia/MG, for 15 days for validation of the computational model. Tar throughout the 24 simulated hours remained higher in DI if compared to the residential section, reaching up to 1.3o C higher in the early morning. A higher vegetation rate present in the DI was not able to overcome the effect of the high rate of waterproofing by asphalt and the roofs of the large warehouses, made up of tiles uncoated metals, which tend to retain heat and have thermal emissivity low. Data from the A 507 meteorological station located at the airport of Uberlândia to estimate UHI intensity, with UHI intensity in DI being 70% higher than the residential segment. The conclusions obtained point to the difficulty of implementation of traditional mitigating measures in industrial districts, whether for limitation of physical space or feasibility of necessary interventions. Actions like replacement of construction materials already implemented by materials with properties adequate thermal temperatures, present themselves as viable alternatives to mitigate the effects of UHIs, mainly regarding the increase in nighttime Tar in industrial districts studied. Urban planning focused on the orientation of streets and avenues to optimize the circulation of winds, and allow penetration into the urban fabric, as well as the increase of the albedo of roofs and floors, can also be interesting alternatives for the mitigation of UHIs in industrial areas. The application of acrylic paints in roofs and surfaces of buildings, or the replacement of parking lot floors and maneuvering yards with permeable floors and open spaces are also alternatives that should guide construction guidelines for industrial districts, especially in cities with tropical climate. The integration between urban planning, on the part of the administration public sector, and companies present in DIs, can transform in the long term, the process of occupation of urban industrial zones focused only on optimizing production industrial. Initiatives that involve public authorities, the population affected by the conditions deteriorated thermal comfort and the interests of industries must converge towards establish processes that effectively integrate such spaces into the urban environment of the point from a climatological point of view. Transformations in urban district planning concepts Industrial industries must contribute to thermal relief and mitigate the effects of UHI in cities.
Formation of Urban Heat Islands in industrial areas
Keywords: Ilhas de Calor Urbanas; Distritos industriais; ENVI-met; Urban heat island; Industrial districts; ENGENHARIAS::ENGENHARIA CIVIL